Clinicopathological evaluation of Autoimmune skin diseases in dogs (Indian Journal of Veterinary Pathology, 2026)
Autoimmune skin diseases in dogs are uncommon but clinically important disorders arising from immune-mediated injury to epidermal, vascular or melanocytic structures. The present study was undertaken to document the clinicopathological features of autoimmune skin diseases in dogs and to establish diagnostic patterns essential for accurate identification. A total of 2,811 dogs presented to the Madras Veterinary College Teaching Hospital, Chennai, were screened for a period of one year (2024-2025). Detailed diagnostic evaluation including clinical examination, dermatoscopy, cytology, haematology, serum biochemistry and histopathology was carried out in suspected cases. Twelve dogs (0.43%) were diagnosed with autoimmune skin diseases, comprising pemphigus foliaceus, pemphigus vulgaris, ear-tip vasculitis and vitiligo. Pemphigus foliaceus presented with crusts, scales and superficial erosions and subcorneal pustules in histopathology, whereas pemphigus vulgaris exhibited severe mucosal ulceration and acantholytic cells on cytology. Ear-tip vasculitis showed ischemic necrosis with fibrinoid vascular changes, while vitiligo was characterized by distinct depigmentation with loss of melanocytes. Dermatoscopic, cytological and histopathological findings supported clinical diagnosis. Haematological and biochemical alterations were mild and not clinically significant. The study highlights that comprehensive clinicopathological evaluation is essential for the early and reliable diagnosis of autoimmune dermatological disorders in dogs.